ANALISIS SEMIOTIKA DALAM NOVEL PULANG-PERGI KARYA TERE LIYE - Kiki Arista Desiana; Yusra D; Sophia Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the semiotic signs in the novel Pulang Pergi by Tere Liye using Charles Sanders Peirce's theory. The novel Pulang Pergi was chosen because it is part of a popular series that presents criminal actions with an international backdrop and successfully captivates readers with its dynamic storyline. Semiotic studies place literary works as structures of signs that hold meaning behind the sequence of words and symbols. Through a qualitative descriptive method, this study aims to identify the trichotomy of icons, indexes, and symbols in the novel and interpret the meanings contained within them. The results of the analysis show that the novel Pulang Pergi uses icons in the form of visual representations and resemblance, indexes in the form of causal relationships between events and character reactions, and symbols derived from social conventions.